2014
DOI: 10.1586/14760584.2014.897615
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of high-risk paediatric populations: Central European Vaccination Awareness Group recommendations

Abstract: Over the last decade, childhood immunization has substantially reduced morbidity and mortality from vaccine-preventable diseases. However, particular paediatric risk groups, such as those with comorbidities, may not be adequately vaccinated despite being more susceptible to complications and death from certain infectious diseases. This may be due to lack of immunization recommendations, lack of awareness, or incomplete adherence to existing guidelines. Furthermore, recommendations for immunization can be incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…Recommendations from the Central European Vaccination Awareness Group, published in 2014, aim to raise awareness and formalize guidance on immunization in high-risk pediatric populations across central Europe [52].…”
Section: Vaccination Programs and Coveragementioning
confidence: 99%
“…Recommendations from the Central European Vaccination Awareness Group, published in 2014, aim to raise awareness and formalize guidance on immunization in high-risk pediatric populations across central Europe [52].…”
Section: Vaccination Programs and Coveragementioning
confidence: 99%
“…Since IPD (including meningitis) is a vaccine-preventable illness [ 2 , 12 , 13 ], vaccination against S. pneumonia in patients with cochlear implants is important and recommended universally [ 13 , 14 ]. WHO recommends the use of pneumococcal conjugate vaccines in all countries and considers their use to be a priority in all national immunization programs [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are two types of pneumococcal vaccines on the market: a 23-valent polysaccharide vaccine (PPV23) and three conjugate vaccines: 7-valent (PCV7), 10-valent (PCV10), and 13-valent (PCV13) [ 2 ]. However, the availability of vaccines, and national immunization programs or vaccination strategies, varies between European countries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been a long-term issue for children with uncontrolled epilepsy and progressive neurological diseases may not be adequately vaccinated. 24 The main concern among this special group is that the vaccine may trigger the recurrence of seizure. 25 A multicentred healthy-control prospective study of adults in China found no evidence suggesting worsening seizures after inactivated COVID-19 vaccination in adults.…”
Section: Discussionmentioning
confidence: 99%